1992
DOI: 10.1302/0301-620x.74b6.1447249
|View full text |Cite
|
Sign up to set email alerts
|

Upper-limb surgery for tetraplegia

Abstract: Violence 1 team which included two upper-limb surgeons, a paraplegist and a hand therapist. The assessment variables included muscle charts (MRC scale), joint mobility, spasm, sensation, motivation and functional requirements. A retrospective review of muscle and sensation charts made it possible to classify 69 of the 84 hands that had had surgery (Table II) according to the international

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
7

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(92 citation statements)
references
References 0 publications
2
83
0
7
Order By: Relevance
“…Lamb and Chan 2 report 27 complications in a series of 41 patients, Mohammed et al, 9 27 complications in 57 patients, and Vanden Berghe, 5 seven complications in 13 patients. In the present study too, 12 complications were observed in nine of the 22 patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Lamb and Chan 2 report 27 complications in a series of 41 patients, Mohammed et al, 9 27 complications in 57 patients, and Vanden Berghe, 5 seven complications in 13 patients. In the present study too, 12 complications were observed in nine of the 22 patients.…”
Section: Discussionmentioning
confidence: 97%
“…1 ± 15 It is rare, however, for authors to give any details on how such measures a ect activities of daily living (ADL) or how patients themselves feel about the results. 2,5,9 The papers on the e cacy of implanted neuroprostheses 12 ± 15 were the ®rst to give any detailed information on ADL and patient satisfaction levels. The object of the present study is to illustrate the e cacy of this functional surgery in the upper extremities of tetraplegic patients by reporting what ADL patients were able to complete without help from others before and after such surgery and how the patients themselves assess the results.…”
Section: Introductionmentioning
confidence: 99%
“…Although we measured the strength of the key-pinch and the grasp we have focused our attention on the functional and psychological results of the surgery, that is to say on the improvement of the performance of the ADL, on the patients' satisfaction, and on the ful®lment of their expectations. These last two items are included in the Mohammed et al scale 18 but we thought it was worthwhile to consider them separately.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, none of the versions of the WHO framework have been used to interpret the different levels of functioning or to consider the clinical usefulness of the measures used specifically for a group of persons who are greater than 10 years post-surgery. Consideration of the ICIDH-2 12 in relation to QoL ( Figure 3) provided the opportunity for consideration of the results of the study described in this commentary, across three different levels of functioning.…”
Section: Clinical Context: Forearm Tendon Transfer Surgerymentioning
confidence: 99%